The Role of Moderating Audit Quality on Income Smoothing - Widyawati, Irma; Trisnawati, Rina (E-Jurnal Akuntansi, 2025)
This study seeks to provide empirical data on the impact of cash holding, income tax, and dividend policy on income smoothing with audit quality as moderation in companies included in the LQ 45 index traded on the Indonesia Stock Exchange from 2019 to 2023. Based on the purposive sample method, sample of 158 companies was obtained within 5 years of research. Logistic regression and moderating analysis are used as data analysis techniques in this study. The findings of this study prove that income tax has a positively affects income smoothing, however cash holding and dividend policy do not impact on income smoothing. Furthermore, on basis of contingency theory, this study utilizes the audit quality metric score which comprises audit firm size, audit firm industry specialization, audit tenure, client importance, and going-concern audit opinion. This study empirically reveals that audit quality can moderating the effect of cash holding and dividend policy on income smoothing. Keywords: Cash Holding; Income Tax; Dividend Policy; Income Smoothing; Audit Quality